Pengaruh Concept Attainment Terhadap Hasil Belajar IPA : (The Effect Of Concept Attainment On IPA Learning Outcomes) - Widiya Septian Dewi Widiya; Sri Wardhani; Rusdy A Siroj (BIODIK, 2021)
This research is motivated by several statements which state that CAM can have a positive effect on learning outcomes. The purpose of the study was to determine whether there was a difference in the effect of applying the concept attainment model on student learning outcomes in science subjects on the structure and function of plant tissue when compared to the lecture method for class VIII SMP Negeri in Kisam Tinggi District, OKU Selatan Regency. The research method used is an experimental design with a quasi-experimental design type Nonequeivalent control group design. The population of this study were all eighth grade students of SMP Negeri in Kisam Tinggi District which consisted of 2 schools. The sample at SMP 1 Kisam Tinggi for the experimental class is VIII E while the control class is VIII B. The sample used at SMP 2 Kisam Tinggi for the experimental class is VIII B while the control class is VIII A. The sampling technique used was purposive sampling. Collecting data with a written test that is by giving a pretest and posttest. The results of the study the average posttest value of the experimental class was 76.00 and the average posttest value of the control class was 51.45. Data analysis was carried out using the Independent Sample T Test with the help of the SPSS 23.0 program. Obtained a significance value of 0.000. The value of sig < 0.005 indicates that H0 is rejected, meaning that there is a difference in the effect of the application of the concept attainment model on the learning outcomes of plant tissue structure and function when compared to the lecture method for class VIII of public junior high schools in Kisam Tinggi sub-district, OKU Selatan district. Abstrak. Penelitian ini dilatar belakangi oleh beberapa pernyataan yang menyatakan CAM dapat berpengaruh positif terhadap hasil belajar. Tujuan penelitian untuk mengetahui apakah ada perbedaan pengaruh penerapan concept attainment model terhadap hasil belajar siswa mata pelajaran IPA materi struktur dan fungsi jaringan tumbuhan jika dibandingkan dengan metode ceramahÂ  kelas VIII SMP Negeri se-Kecamatan Kisam Tinggi Kabupaten OKU Selatan. Metode penelitian yang digunakan adalah eksperimen dengan rancangan quasi experimental design tipe Nonequeivalent control group design. Populasi penelitian ini seluruh siswa kelas VIII SMP Negeri se-Kecamatan Kisam Tinggi yang terdiri dari 2 sekolah. Sampel pada SMP 1 Kisam Tinggi untuk kelas eksperimen yaitu VIII E sedangkan kelas kontrol VIII B, Sampel yang digunakan pada SMP 2 Kisam Tinggi untuk kelas eksperimen yaitu VIII B sedangkan kelas kontrol VIII A. Teknik pengambilan sampel mengunakan purposive sampling. Pengumpulan data dengan test tertulis yaitu dengan cara memberikan pretest dan Posttest. Hasil penelitian nilai rata-rata posttest kelas eksperimen 76,00 dan nilai rata-rata posttest kelas kontrol 51,45 Â Analisis data dengan Independent Sample T Test dengan bantuan program SPSS 23.0. Diperoleh nilai signifikansi sebesar 0,000. Nilai sig < 0,005 hal ini menunjukkan bahwa H0 ditolak artinya terdapat perbedaan pengaruh penerapan concept attainment model terhadap hasil belajar materi struktur dan fungsi jaringan tumbuhan jika dibandingkan dengan metode ceramah